(untitled) - Slater, P. J. B. (Cambridge,New York, 1999)
Essentials of Animal Behaviour is an introduction to the study of animal behavior that is primarily intended for first- or second-year undergraduates. The book aims to get across the basic principles of the subject as briefly and lucidly as possible with the aid of carefully selected examples from both recent and classic research, together with numerous illustrations. The text will stimulate readers with its active and exciting treatment of the research, and will lay a solid foundation on which further study may be based. Its simple and readable style, helped by an extensive glossary, will make it useful and enjoyable reading for all those with an interest in the subjects of animal behavior, behavioral ecology, and comparative psychology.
Keywords: Animal behavior,Tập tính của động vật